PENGARUH SIKAP KERJA, KETERAMPILAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Affandi, Muhammad Ery; Andriani, Dewi (Universitas Bina Taruna Gorontalo, 2024)
This research aims to determine the influence of work attitudes and work environment on employee performance. This research uses a quantitative approach as a research method. The population of this study consists of all employees. This research uses a total sampling technique. The data used in this research consists of primary data, which was obtained through distributing questionnaires to respondents. Quantitative data analysis techniques using statistical methods to analyze data. The statistical method used is SPSS 26. Based on the research results, the work attitude variable is 3.180. The ttable value with a significance level of 0.05 is 1.979. Therefore, tcount > ttable (3.180 > 1.979), and the significance value is 0.002 < 0.05. The t-count value for the work skills variable is 4.451. The ttable value with a significance level of 0.05 is 1.979. Therefore, tcount > ttable (4.451 > 1.979), and the significance value is 0.000 < 0.05. So the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that partially there is a significant influence between work skills and employee performance. For the work environment variable it is 3.690. The ttable value with a significance level of 0.05 is 1.979. Therefore, tcount > ttable (3.690 > 1.979), and the significance value is 0.000 < 0.05. Which can show a significant work attitude towards the work environment.